The Effects of Holocene Landscape Changes on the Formation of the Archaeological Record in the Fayum Basin, Egypt. Issue 1 (January 2016) - Koopman, Annelies; Kluiving, Sjoerd; Holdaway, Simon; Wendrich, Willeke
Abstract : Geoarchaeological research was performed across an archaeological landscape along the hyperarid northern paleoshores of the modern Lake Qarun, Fayum Basin, Egypt. Objectives were to record sedimentary variability and to consider the correlation between the paleoenvironmental interpretations of these sedimentary data and the observed archaeological record dated to the early and mid‐Holocene. Our approach combines hand‐drilling and stratigraphic descriptions with detailed studies of sediments (grain size analysis, analyses of CaCO3, and organic matter contents), densities of stone artifacts and bones, and chronometric data from associated contexts (AMS 14 C dates on charcoal from hearths). Analysis of deposits indicates initiation of lake deposition, reworking of lake deposits, and subsequent accumulation of wind‐blown deposits occurred prior to the deposition of archaeological materials. Correlations between sediment and the archaeological deposits indicate a different use of areas covered by relatively coarse‐grained sediment (sand) compared to areas where relatively fine‐grained deposits are exposed (clay and silt). Reassessment of the associations between archaeological materials and sediments in the Fayum Basin is required to improve knowledge of the interrelationships between the Nile flood history, regional climatic changes, oscillations in levels of paleo‐Lake Qarun, compared to the chronology of human occupation in the Fayum Basin.